A Buddhist manuscript of ‘The hundred-syllable mantra of Vajrasattva’ in Oirat language from the National Museum of Tuva - Mandzhieva, Bayrta B.; Sumba, Rita P. (The New Research of Tuva, 2019)
The article introduces (both in transliteration and translation into Russian) the handwritten Buddhist text ‘The hundred-syllable mantra of Vajrasattva’, preserved in the collection of the National Museum of the Republic of Tuva. The text is a part of an Oirat manuscript known as “Ekeyin zürken tarni orošiboi” (‘Hridaya-dharani of Mothers’). It is remarkable in its representation of the famous Buddhist hundred-syllable mantra of Vajrasattva, which has been practiced by Buddhists from ancient times to the present day.Vajrasattva is a Buddha of Vajrayana, a symbol of purity of Enlightenment (Bodhi) and the Law (Dharma). Reading the sacred hundred-syllable mantra for Buddhists has magical significance: if read one hundred and eight times, it cleans the heavy karma of a person; if pronounced a million times, it gives enlightenment. The hundred-syllable mantra is believed to be above all other mantras, therefore Buddhist lamas say that there is no deeper practice than the ‘The hundred-syllable mantra of Vajrasattva’.
Keywords: Buddhism; manuscript; Oirat language; hundred-syllable mantra; Vajrasattva; National Museum of the Republic of Tuva; Tuva